2011
DOI: 10.5530/ijmedph.3.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Adolescents’ Health Beliefs and Health Behavior

Abstract: a b S t r a c tAim: this study aims to determine the relationship between Health behavior and Health locus of control among 1270 adolescents (boys n = 635 and girls = 635) who were drawn from bangalore rural and urban district government high schools (mean age 13.76 years). Methodology: the global School based Health survey (WHo, 2004) and Multidimensional Health locus of control by Wallston and Wallston, questionnaires were used to assess health locus of control and health behavior respectively. the data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Therefore, it is expected that individuals who think that he or she can compensate for unhealthy behaviour such as drinking, and smoking are less likely to engage in health-risk behaviour thereby improving their QoL (Nooijer, et al 2009). This finding is also in support of the studies of Shabaraya, Romate and Bhogle (2011) who argued that health beliefs have a relationship with health behavior.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it is expected that individuals who think that he or she can compensate for unhealthy behaviour such as drinking, and smoking are less likely to engage in health-risk behaviour thereby improving their QoL (Nooijer, et al 2009). This finding is also in support of the studies of Shabaraya, Romate and Bhogle (2011) who argued that health beliefs have a relationship with health behavior.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of the study indicated that compensatory health beliefs significantly predicted QoL in the oil spills prone communities, such that participants with higher compensatory heath beliefs pertaining to their behaviour were more likely to experience better QoL. This outcome is in line with the findings by Aliha (2015); Dogan et al (2018) and Shabaraya, Romate and Bhogle (2011) who argued that health beliefs have a relationship with QoL. This implies that individuals who justify their unhealthy choices in the process of anticipating for healthy ones will be less vulnerable to diseases and illness such as diarrhea, cholera, and malaria, which is common in the riverine oil communities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Adolescents who used condoms in their first sexual intercourse showed greater internalization, evidencing a greater capacity for sexual negotiation with partners (9,22) . In another study, internal adolescents and with greater External locus of control (Powerful Others) had healthier dimensions of positive behaviors, which shows that health behavior is not correlated with beliefs in health being a matter of chance (23) .…”
Section: Discussionmentioning
confidence: 95%
“…This issue is generally associated with internal locus of control. Subsequently, internal locus of control can result in a healthy lifestyle in high-risk populations (10).…”
Section: Discussionmentioning
confidence: 99%